Prophylaxis of Thromboembolic Disease and Platelet-Related Changes Following Total Hip Replacement: A Comparative Study of Aspirin and Heparin-Dihydroergotamine - Alfaro, M J; Páramo, J A; Rocha, E (Thrombosis and Haemostasis, 1986)
A prospective study involving 120 consecutive patients undergoing total hip replacement was performed to compare the effectiveness of aspirin (high and low dose) or a combination of heparin plus dihydroergotamine (heparin-DHE) in preventing isotopic and phlebographic deep vein thrombosis (DVT), and to evaluate their effect on postoperative platelet changes. Phlebographic DVT was demonstrated in 9 cases (30%) in control group, in 1 (3.3%) in aspirin (high-dose) group (p <0.01), in 1 (3.3%) in aspirin (low-dose) group (p <0.01) and in 5 (16.6%) in heparin-DHE group (p = NS). Aspirin was able to reduce the postoperative increase in circulating platelet aggregates, platelet factor 4 and p-thromboglobulin observed in control group. This study shows that aspirin is effective in the prevention of DVT for patients undergoing total hip replacement. Small aspirin dose (250 mg/day) represents an effective form of prophylaxis in these patients.
Keywords: Postoperative deep vein thrombosis; Aspirin; Heparin; dihydroergotamine